Optimization of wet method synthesis of sodium percarbonate: Effect of Mass Ratio and Stabilizer Composition - Hasni, Hasni; Farmawaty, Farmawaty (Journal of Health, Education, Economics, Science, and Technology, 2025)
Sodium percarbonate is a crystalline compound widely used as an eco-friendly bleaching and oxidizing agent. This study aims to synthesize sodium percarbonate using the wet method by examining the effects of rmass ratio and stabilizer dosage on product quality. The synthesis was carried out by variated the mass ratio of sodium carbonate to hydrogen peroxide and applying a composite stabilizer. The product was evaluated based on active oxygen content, yield, and stability. The results indicate that the optimal mass ratio is 1:1, yield product is 68.64% with 13.58% active oxygen content. The best product quality was obtained using a composite stabilizer composed of sodium silicate, magnesium sulfate heptahydrate, and triethanolamine, with an optimal dosage of approximately 1%.